Triple oxygen isotope measurements by tunable infrared laser direct absorption spectroscopy, and applications to ratite eggshell - Yarian, Drake (Department of Archaeology, 2024)
This project introduces a new sample preparation technique and analytical methodology for highprecision measurement of the three oxygen isotopes directly in CO2 samples using Tunable Infrared Laser Direct Absorption Spectroscopy (TILDAS). After the introduction and optimization of both the sample preparation and analytical systems, it is applied to fossil ratite eggshell (RES) samples spanning the mid-Miocene through Quaternary Namib environments. A data correction scheme for relating TILDAS measurements to the VSMOW2-SLAP2 scale is also introduced. Applying this correction, analyses of the international CaCO3 standards IAEA603, NBS18, and NBS19 are shown to agree well with previously reported values. In addition, Δ'17O 1σ reproducibilities of 10, 19, and 60 per meg (1 per meg = 0.001‰) of these standards, respectively, are achieved. Analysis of RES suggests notable environmental differences between the central and southern Namib through time. RES D' 17O signal preservation in the context of global climatic and local environmental influences is investigated by relating obtained data to current triple oxygen enabled atmospheric and animal body water models. This project concludes by recommending 3 main points of focus for future research directed towards improving RES data interpretation within the context of (paleo-)environmental reconstruction: (1) adoption of international standards with composition representative of RES, (2) dedicated research into the influence vegetation type has on leaf water D' 17 O, and (3) a community-wide increase in analyses of modern RES D' 17 O data to provide a better foundation from which paleoclimatic and paleoenvironmental interpretations may be made.